2012
DOI: 10.1002/bies.201100150
|View full text |Cite
|
Sign up to set email alerts
|

MHC‐dependent mate choice in humans: Why genomic patterns from the HapMap European American dataset support the hypothesis

Abstract: The role of the major histocompatibility complex (MHC) in mate choice in humans is controversial. Nowadays, the availability of genetic variation data at genomic scales allows for a careful assessment of this question. In 2008, Chaix et al. reported evidence for MHC‐dependent mate choice among European American spouses from the HapMap 2 dataset. Recently, Derti et al. suggested that this observation was not robust. Furthermore, when Derti et al. applied similar analyses to the HapMap 3 European American sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
1
20
1
Order By: Relevance
“…In effect, ethnic heterogeneity within a sample will produce patterns of positive assortative mating at the ethnic level, where spouses are more similar at a genomewide level than random pairs of individuals (Chaix et al . ; Laurent & Chaix ). We found strong support for this explanation in our findings of significant effects for similarity within couples sampled from ethnically heterogeneous populations, but not from homogeneous populations or from experimental studies that control for potential ethnic biases (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In effect, ethnic heterogeneity within a sample will produce patterns of positive assortative mating at the ethnic level, where spouses are more similar at a genomewide level than random pairs of individuals (Chaix et al . ; Laurent & Chaix ). We found strong support for this explanation in our findings of significant effects for similarity within couples sampled from ethnically heterogeneous populations, but not from homogeneous populations or from experimental studies that control for potential ethnic biases (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A way to rule out spurious MHC associations stemming from population stratification – differences in subpopulation background allele frequencies (Cardon & Palmer ; Derti et al . ; Laurent & Chaix ) – would be to provide measures of neutral genetic similarity of couples. One study adopting this design was able to determine that MHC dissimilarity in couples of European ancestry was independent of genomewide effects, while MHC similarity observed in couples of Yoruban ancestry was most likely a consequence of kinship‐based assortative mating (Chaix et al .…”
Section: Discussionmentioning
confidence: 99%
“…Two nonhuman primate studies tested for mate choice for optimal diversity and found nonsignificant results 89,135 and two human studies found suggestive evidence of selection for optimal offspring diversity. Derti et al compared genome-wide single nucleotide polymorphisms (SNPs) between European-American mates and found some evidence that partners avoid extreme similarity at MHC genes 86 (though another study using overlapping datasets have interpreted these results to support MHC-dissimilarity 85,136 ); Jacob et al found that women preferred odors of men with more alleles matching those inherited paternally, but not maternally, 54 suggesting that women employ an odor preference that provides them optimal allele matching.…”
Section: Selection For Intermediate Dissimilarity and Diversitymentioning
confidence: 99%
“…86,136,[140][141][142][143][144][145][146] In fact, of the 27 studies on human MHC-associated mate selection reviewed here, one-third (nine studies) have provoked direct criticism and published correspondence between authors and critics (Table S1). These discussions conclude that the most critical factor to consider is context, including within and among individuals and within and among populations.…”
Section: Conclusion Caveats and Recommendationsmentioning
confidence: 99%
“…However, the statistical methods of testing their hypothesis was criticized, because the significance could be attribute to extreme mate pairs within the groups, as well as for not correctly adjusting their statistical thresholds for multiple hypothesis testing (Derti et al, 2010). After adjusting their previous results for multiple hypotheses (Laurent and Chaix, 2012), the critics agreed (Derti and Roth, 2013) that MHC based mate selection was an apparent, but not a robust result, which might simply be attributed to the small sample size. Further research is certainly called for on the role of VOC given off by MHC compounds in humans in the selection of mates across cultures.…”
Section: Olfactory Sensory States Are Phenomenally Consciousmentioning
confidence: 96%